Prune belly syndrome: a case of early prenatal diagnosis - Kamra, Suvidhi; Santpur, Unmesh; Puri, Nidhi; Pippet, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Prune belly syndrome is a rare congenital disorder typically characterized by a triad of malformation of the urogenital tract, defect of abdominal wall musculature, and cryptorchidism. The condition is generally incompatible with life as infants born with this syndrome are either stillborn or die within the first few weeks of life. The present case is of a fetus presenting with prune bell syndrome, detected in first trimester of pregnancy.